English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
2

a/3 + 3 = 12 =

y/4 +2 = -1 =

Find the missing term in the following pattern.
1, 2, 6, 24, 120, ______

2007-07-26 06:04:20 · 11 answers · asked by x3iiloveuux3 1 in Science & Mathematics Mathematics

11 answers

a= 27

y = -12

missing 720

2007-07-26 06:09:54 · answer #1 · answered by Ali 2 · 0 0

Find the missing term in the following pattern.
1, 2, 6, 24, 120, 720 since each subsequent term is multiplied by n+1 where n is the number of the present term (not its value).

a/3 + 3 = 12

a/3 = 12 - 3 = 9

a = 27

y/4 + 2 = -1

y/4 = -1 - 2 = -3

y = - 12

2007-07-26 13:11:07 · answer #2 · answered by Swamy 7 · 0 0

to find a in the first equation you would first subtract 3 from both sides: a/3=9. then multiply by 3. you get a=27.

the second equation subtract 2: y/4=-3 multiply by 4 and you get y=-12

the pattern is multiply by 2, x3, x4,x5 the next would be times 6 so multiply 120 times 6, you get 720.

I hope that helped.

2007-07-26 13:10:26 · answer #3 · answered by over-achiever 2 · 0 0

a/3 = 12-3 = 9
a = 9*3 = 27

y/4 = -1-2 = -3
y = -3*4 = -12

1, 2, 6, 24, 120, ______120*6 = 720

2007-07-26 13:07:14 · answer #4 · answered by sahsjing 7 · 0 0

a/3 + 3 = 12
a/3 = 12 - 3
a/3 = 9
a = 9 * 3
a = 27

y/4 + 2 = - 1
y/4 = - 1 - 2
y/4 = - 3
y = - 3 * 4
y = - 12

Missing term might be 720.
1 * 2
2 * 3
6 * 4
24 * 5
120 * 6
720 * 7
5040 * 8

The multiplier increases 1 each time and multiplied with the product.

2007-07-30 11:41:03 · answer #5 · answered by Jun Agruda 7 · 2 0

a/3 + 3 = 12
Multiply everything by GCF of denominators of the whole problem (3) and get -->
a + 9 = 36
-9 -9 (SUBTRACT 9 ON BOTH SIDES)
a = 27
___________________________________
y/4 + 2 = -1
Multiply everything in the equation by the denominator, 4, and then you get:
y + 8 = -4
- 8 -8 (SUBTRACT 8 ON BOTH SIDES)
y = -12
___________________________________
The missing term in the final one is 720
The pattern is thus:
The first pair you multiply by 2 to get the second one.
The second pair (2, 6) you multiply by three to get the next term
The third pair (6, 24) you multiply by four to get the next term
The fourth pair (24, 120) you multiply by five to get the next term
etc.

2007-07-26 13:15:00 · answer #6 · answered by Dan 2 · 0 0

Missing term is 720

2007-07-26 13:07:25 · answer #7 · answered by Anonymous · 0 0

the first term is 1*n and all the once after is the previous term*(n+1) with n=1

120*6

2007-07-26 13:07:49 · answer #8 · answered by Anonymous · 0 0

The missing number is 720. Because you times the number increasing by one each time!

A = 27

Y = -12

Hope this has helped =)

2007-07-26 13:11:27 · answer #9 · answered by Anonymous · 0 0

the missing term is 720

2007-07-26 13:08:55 · answer #10 · answered by :] 2 · 0 0

fedest.com, questions and answers